The participation of the Ukrainian deputies of the Parliament of the Habsburg monarchy in the creation of Ukrainian educational, economic, and military organizations on the territory of Eastern Galicia - Baran, Anzhelika (Actual problems of law (Aktual’ni problemi pravoznavstva), 2018)
The article analyzes some aspects of the parliamentary activities of the Ukrainian deputies regarding the creation of the krainian educational, economic, and military formations on the territory of Eastern Galicia beginning of XX century Determined that the struggle for the key for the Ukrainian segment of the population of Austria-Hungary the right to create their own educational, economic, and military forces conducted exclusively legal methods.